Use of sanitizing products: safety practices and risk situations - Ana Aurélia Rocha da Silva; Raquel Souza Passos; Luiz Alberto Simeoni; Francisco de Assis Rocha Neves; Elisa de Carvalho (Brazilian Society of Pediatrics, 2014)
Objectives: to evaluate the handling and risk factors for poisoning and/or digestive tract injuries associated with the use of sanitizing products at home. Methods: interviews were conducted in 419 households from different regions, collecting epidemiological data from residents and risk habits related to the use and storage of cleaning products. Results: sanitizing products considered to be a health risk were found in 98% of the households where the research was conducted, and in 54% of cases, they were stored in places easily accessible to children. Lye was found in 19%, followed by illicit products in 39% of homes. In 13% of households, people produced soap, and in 12% they stored products in non-original containers. The use of illicit products and the manufacture of handmade soap were associated with lower educational level of the household owners and with the regions and socioeconomic classes with lower purchasing power. Conclusions: risk practices such as inadequate storage, manufacturing, and use of sanitizing products by the population evidence the need for public health policies, including educational measures, as a means of preventing accidents.